Mechanical Properties Characterization of Welded 3CR12 Stainless Steel - Thabo Mathonsi (ITEGAM-JETIA)
The use of metal inert gas (MIG) welding for joining metals frequently results in the change of the mechanical properties and the microstructure of the metal at the welded areas. This is due to the welding heat input and heat transfer.  3CR12 is a low-cost special stainless steel containing 12% chromium. It is considered to have good mechanical properties and corrosion resistance as a base metal, and understanding how these properties change as a result of MIG welding enables the drawing of proper conclusions regarding the properties of MIG welded 3CR12 stainless steel.  However, little is known about its properties and behavior after welding with metal inert gas (MIG) welding, which is the most common welding process for welding stainless steel, and little is known about its weldability.  Due to inadequate information about MIG welded 3CR12 stainless steel, it is hard to make a reliable statement about its properties and behavior. Thus, necessitating the need to gain knowledge regarding MIG welded 3CR12 stainless steel. This paper aims to characterize the mechanical properties of welded 3CR12 stainless steel. The focus is on investigating how the mechanical properties and the microstructure of 3CR12 stainless steel evolve due to MIG welding.